2017
DOI: 10.1038/ismej.2017.168
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of antibiotic-inactivating enzyme driven by ecology expands the environmental resistome

Abstract: The environmental resistome has been recognized as the origin and reservoir of antibiotic resistance genes and considered to be dynamic and ever expanding. In this study, a targeted gene sequencing approach revealed that the polymorphic diversity of the aminoglycoside-inactivating enzyme AAC(6')-Ib was ecological niche-specific. AAC(6')-Ib-cr, previously known as a clinical variant, was prevalent in various soils and the intestines of chickens and humans, suggesting that this variant might not have arisen from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 56 publications
2
16
1
Order By: Relevance
“…Among >130,000 bacterial genomes available in March 2018 from the NCBI genome database, including both complete and draft genomes, a total of 3,964 aac(6′)-Ib gene sequences (370 and 3,594 from complete and draft genome databases, respectively) were found to be present in the bacterial genomes. The relative abundance and Shannon entropy analysis of polymorphism in the AAC(6′)-Ib proteins revealed that three residues (102, 117, and 179) were prominent polymorphic residues ( Figure 1 ), as previously shown by the metagenomic studies conducted at various environmental sites ( Kim et al, 2018 ). Composition of AAC(6′)-Ib variants (Ib, IbL, and cr) were highly similar in the complete and draft genome databases ( Supplementary Figure 1 ).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Among >130,000 bacterial genomes available in March 2018 from the NCBI genome database, including both complete and draft genomes, a total of 3,964 aac(6′)-Ib gene sequences (370 and 3,594 from complete and draft genome databases, respectively) were found to be present in the bacterial genomes. The relative abundance and Shannon entropy analysis of polymorphism in the AAC(6′)-Ib proteins revealed that three residues (102, 117, and 179) were prominent polymorphic residues ( Figure 1 ), as previously shown by the metagenomic studies conducted at various environmental sites ( Kim et al, 2018 ). Composition of AAC(6′)-Ib variants (Ib, IbL, and cr) were highly similar in the complete and draft genome databases ( Supplementary Figure 1 ).…”
Section: Resultssupporting
confidence: 79%
“…Moreover, in this study, the presence of the cr variant was found to be correlated with the presence of IbL variant ( R 2 = 0.88) ( Supplementary Figure 2 ), suggesting that the mutation at L117 might be a prerequisite for the emergence of the cr variant, and evolution of these variants might be associated with each other. Other polymorphic variants of aac(6 ′ )-Ib such as R102/L117 and L117/Y179 variants, which were previously characterized to confer altered resistance spectra ( Kim et al, 2018 ), were detected mainly in the genera Klebsiella and Enterobacter ( Supplementary Table 1 ), indicating that these novel variants discovered in various environments were indeed present in clinical isolates.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations